The Significance of the Legislative Resolutions of International Organizations for the Development of International Law - Skubiszewski, Krzysztof (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Uchwały prawotwórcze organizacji międzynarodowych: przegląd zagadnień i analiza wstępna by Krzysztof Skubiszewski, published originally in Polish in “Ruch Prawniczy, Ekonomiczny i Socjologiczny” in 1965. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.